Kriminalisasi Deepfake sebagai Bentuk Kejahatan Internasional Baru dalam Perspektif Hukum Pidana Internasional - Alip Asya Hidayat; Wevy Efticha Sary (Lembaga Yasin AlSys, 2026)
The development of artificial intelligence technology, particularly deepfake, has transformed the landscape of digital crime because its impact not only harms individuals but also has the potential to disrupt social, political, and international security stability. However, legal regulations that explicitly govern the misuse of deepfake within the framework of international criminal law are still unavailable. This study aims to analyze legal regulation of deepfake from the perspective of international criminal law and to examine the urgency of its criminalization as a new form of international crime. This study used a normative legal method with a statute approach and a conceptual approach. The legal materials used included primary legal materials in the form of international legal instruments and secondary legal materials in the form of books, journals, and relevant scientific literature. The results showed that legal regulation of deepfake in international criminal law remains indirect and has not provided adequate legal certainty. Deepfake has not yet been recognized as a stand-alone international crime but is still positioned as a means of committing other crimes. This normative gap creates various problems, including difficulties in law enforcement, jurisdictional conflicts, and challenges in proving and attributing perpetrators. The findings of this study confirm that the criminalization of deepfake as a new international crime needs to be considered because of its broad impact on human rights, social stability, and international security. Deepfake meets the criteria as an emerging international crime because it causes significant harm, violates universal values, and requires international cooperation in its handling. Thus, reform of international criminal law that is adaptive to developments in digital technology is needed through the formulation of a specific legal instrument on deepfake to provide legal certainty and effective protection for the international community.